Difficulties of Programming Learning from the Point of View of Students and Instructors - Bosse, Yorah; Gerosa, Marco Aurelio (Revista IEEE América Latina, 2017)
Computer programming courses are mandatory for many majors. However, the high rate of failures shows that students have difficulties in assimilating the topics. The objective of this research is to understand these difficulties. Analyzing diaries filled out by students and interviews with instructors, we identified difficulties related to language and understanding and some strategies used to mitigate them. The analysis and understanding of the difficulties may support the creation of teaching strategies and tools to facilitate the teaching and learning of computer programming.